A companion to media authorship - Gray, Jonathan (Jonathan Alan); Johnson, Derek, 1979- (Malden, MA : Wiley Blackwell, 2013)
"A Companion to Media Authorship offers 28 groundbreaking chapters which investigate the practices, attributions, and meanings of authorship. Revitalizing the study within media and cultural studies, this diverse and global collection provides the definitive work on the subject.-Rethinks cultures of authorship and challenges the concept of auteurism across multiple media forms -Moves beyond notions of the individual to focus on how authorship is collaborative, contested, and networked, examining cultures of authorship and the practicalities of how it works -Draws on the cutting-edge research of scholars and practitioners whose work has produced significant new insights into the field -Examines a wide range of media, including television, social media, radio, videogames, transmedia, music, and comic books -Offers an impressive global focus, including pieces on Mexican music, amateur film production in Nairobi slums, tele-serial production in Kinshasa, Hong Kong film, and the marketing of Bollywood"--
Machine generated contents note: 1. Introduction: The Problem of Media Authorship (Jonathan Gray and Derek Johnson) I. Theorizing and Historicizing Authorship 2. Authorship and the Narrative of the Self (John Hartley) 3. The Return of the Author: Ethos and Identity Politics (Kristina Busse) 4. Making Music: Copyright Law and Creative Process (Olufunmilayo B. Arewa) 5. When is the Author? (Jonathan Gray) 6. Hidden Hands At Work: Authorship, the Intentional Flux, and the Dynamics of Collaboration (Colin Burnett) II. Contesting Authorship 7. Participation is Magic: Collaboration, Authorial Legitimacy, and the Audience Function (Derek Johnson) 8. Telling Whose Stories? Reexamining Author Agency in Self-Representational Media in the Slums of Nairobi (Brian Ekdale) 9. Never Ending Story: Authorship, Seriality, and the Radio Writers Guild (Michele Hilmes) 10. From Chris Chibnall to Fox: Torchwood's Marginalized Authors and Counter-Discourses of TV Authorship (Matt Hills) 11. Comics, Creators, and Copyright: On the Ownership of Serial Narratives by Multiple Authors (Ian Gordon) III. Industrializing Authorship 12. Benny Hill Theatre: "Race," Commodification, and the Politics of Representation (Anamik Saha) 13. Cynical Authorship and the Hong Kong Studio System: Li Hanxiang and his Shaw Brothers Erotic Films (Stephen Teo) 14. The Authorial Function of the Television Channel: Augmentation and Identity (Catherine Johnson) 15. The Mouse House of Cards: Disney Tween Stars and Questions of Institutional Authorship (Lindsay Hogan) 16. Transmedia Architectures of Creation: An Interview with Ivan Askwith (Jonathan Gray) 17. Dubbing the Noise: Square Enix and Corporate Creation of Videogames (Mia Consalvo) IV. Expanding Authorship 18. Authorship Below-The-Line (John T. Caldwell) 19. Production Design and the Invisible Arts of Seeing (David Brisbin) 20. Scoring Authorship: An Interview with Bear McCreary (Derek Johnson) 21. Bowdown to Your New God: Misha Collins and Decentered Authorship in the Digital Age (Louisa Stein) 22. Collaboration and Co-Creation in Networked Environments: An Interview with Molly Wright Steenson (Megan Sapnar Ankerson) 23. Dawn of the Undead Author: Fanboy Auteurism and Zack Snyder's "Vision" (Suzanne Scott) V. Relocating Authorship 24. Authoring Hype in Bollywood (Aswin Punathambekar) 25. Auteurs at the Video Store (Daniel Herbert) 26. Authorship and the State: Narcocorridos in Mexico and the New Aesthetics of Nation (Hector Amaya) 27. Scripting Kinshasa's Teleserials: Reflections on Authorship, Creativity, and Ownership (Katrien Pype) 28. "We Never Do Anything Alone": An Interview on Academic Authorship with Kathleen Fitzpatrick (Jonathan Gray and Derek Johnson).
Includes bibliographical references and index.
Print version record.
Keywords: Arts -- Authorship; Creation (Literary, artistic, etc.); SOCIAL SCIENCE -- Media Studies; Arts -- Authorship; Creation (Literary, artistic, etc.); Electronic books